Patterns of employment relationships: the association between compensation policy and contractual arrangements - Suleman, F.; Lagoa, S.; Suleman, A. (Global Innovation and Knowledge Academy (GIKA 2015), 2015)
This study examines the employment relationship in large-sized firms in Portugal using linked employer-employee data. It starts with a fuzzy clustering approach to identify typical compensation policies. Three major segments emerge from this analysis: Competitive, Internal Labor Markets, and Incentive. The Competitive segment is highly responsive to market conditions and comprises low-wage firms. The other segments reveal properties of internal labor markets, although the incentive-based firms reinforce the use of discretionary power to differentiate the workforce. Subsequently, a regression model is estimated to analyze the association between compensation policies and contractual arrangements. Empirical evidence confirms the segmentation predictions, that is, low, flexible wages and flexible contracts prevail in the same firms. Furthermore, vulnerable categories like young workers and female workers tend to be over-represented in firms belonging to the Competitive cluster.